The law of cybercrimes and their investigations - Curtis, George E., 1942- (Boca Raton : CRC Press, 2012)
'Presenting a broad-based analysis, this volume explores the many aspects of cybercrime as well as its investigation and prosecution. It begins with an overview of the use of computers and other digital devices to commit traditional computer crimes. Next, it examines cybercrimes against individuals, including those involving obscenity, child pornography, sexual predator conduct, online gambling, and cyberstalking. It also explores identify theft and fraud, data privacy crimes, and ponzi schemes. The book includes a section on the investigation of cybercrimes and covers the applicable laws. Each chapter includes key words and phrases, review problems, and weblinks for further study'--
Crimes involving the use of computers -- Information warfare and cyberterrorism -- Crimes implicating morality -- Crimes threatening or resulting in physical or mental harm -- Internet frauds -- Data privacy crimes -- Intellectual property crimes -- Search and seizure : beginning principles -- Searches and seizure : electronic evidence -- Wiretapping and eavesdropping -- Access to stored communications -- Pen registers, trap and trace devices, and GPS devices -- Digital evidence and forensic analysis -- International issues involving the investigation and prosecution of cybercrime.
Includes bibliographical references (p. 375) and index.
Keywords: Computer crimes -- United States; Computer crimes -- Investigation -- United States